2002
DOI: 10.1016/s0002-9440(10)64176-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Gene Expression Induced by RET with MEN2A or MEN2B Mutation

Abstract: Germ-line point mutations of the RET gene are responsible for multiple endocrine neoplasia (MEN) type 2A and 2B that develop medullary thyroid carcinoma and pheochromocytoma. We performed a differential display analysis of gene expression using NIH 3T3 cells expressing the RET-MEN2A or RET-MEN2B mutant proteins. As a consequence, we identified 10 genes induced by both mutant proteins and eight genes repressed by them. The inducible genes include cyclin D1, cathepsins B and L, and cofilin genes that are known t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
64
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(71 citation statements)
references
References 54 publications
7
64
0
Order By: Relevance
“…The modulation of its expression has been revealed in numerous developmental, physiological and pathological processes. Recently, STC1 has also been reported to be induced in a variety of tumors including the breast (McCudden et al, 2004), colon (Gerritsen et al, 2002), ovary (Ismail et al, 2000), lung cancer (Garber et al, 2001), thyroid medullary carcinoma (Watanabe et al, 2002), hepatocarcinoma (Okabe et al, 2001), pheochromocytoma (Eisenhofer et al, 2004), neuroblastoma (Wong et al, 2002), osteosarcoma and fibrosarcoma (Jellinek et al, 2000). The possible use of STC1 expression levels for the diagnosis of human breast, hepatocellular and colorectal cancer has also been proposed (Fujiwara et al, 2000;Wascher et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The modulation of its expression has been revealed in numerous developmental, physiological and pathological processes. Recently, STC1 has also been reported to be induced in a variety of tumors including the breast (McCudden et al, 2004), colon (Gerritsen et al, 2002), ovary (Ismail et al, 2000), lung cancer (Garber et al, 2001), thyroid medullary carcinoma (Watanabe et al, 2002), hepatocarcinoma (Okabe et al, 2001), pheochromocytoma (Eisenhofer et al, 2004), neuroblastoma (Wong et al, 2002), osteosarcoma and fibrosarcoma (Jellinek et al, 2000). The possible use of STC1 expression levels for the diagnosis of human breast, hepatocellular and colorectal cancer has also been proposed (Fujiwara et al, 2000;Wascher et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The possible use of STC1 expression levels for the diagnosis of human breast, hepatocellular and colorectal cancer has also been proposed (Fujiwara et al, 2000;Wascher et al, 2003). Moreover, it has been shown that the inherited mutations of the RET gene, responsible for the MEN2A and MEN2B, are able to induce STC1 expression (Watanabe et al, 2002). Recently, a critical role of STC1 expression in the formation of tumor vasculature has been proposed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate whether MKP-2 expression is induced by the activation of endogenous RET by GDNF, TGW neuroblastoma cells, which have been shown to express both endogenous RET and GFRa1 (Watanabe et al, 2002;Uchida et al, 2006), were treated with GDNF. MKP-2 was weakly expressed in TGW cells in their basal state, and biphasic induction of MKP-2 was observed 15 min and 6 h after GDNF stimulation Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, it was shown that JNK mediates survival signals after cell transformation by the oncogenic tyrosine kinase BCR-ABL (Hess et al, 2002). In addition, Watanabe et al, (2002) established a number of genes differentially expressed by MEN 2A-RET or MEN 2B-RET. Again, these results imply striking differences in pathways activated by MEN 2B-RET.…”
Section: Retc634rmentioning
confidence: 99%